Investigation into a Link between Students’ English Reading Speed and Reading Comprehension Achievement: The Case of Indonesian EFL Student Teachers - Andri Pratama (Edukasi, 2019)
The aims of the study were to look at the link between English as a foreign language (EFL) student teachers’ reading speed and reading comprehension achievement and whether it influenced their reading comprehension achievement or not. The population of the study was 583 active EFL student teachers in one English Education Study Program at an Indonesian state Islamic University. By using purposive sampling technique, there were 87 students involved as participants in this study. The data were gained by using two kinds of tests, reading speed test and reading comprehension test. Descriptive statistics, Pearson Product Moment Correlation was employed to analyze the data. From the data analyses, it was found that the correlation between EFL student teachers’ English reading speed attitude and their reading comprehension achievement did not exist. As the result, the second problem was eliminated. In short, reading speed did not have any relation to reading comprehension achievement.